1999
DOI: 10.1002/j.2048-7940.1999.tb02190.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuity and Discontinuity: The Quality of Life Following Stroke

Abstract: The purpose of this existential‐phenomenological study was to investigate the experience of life after stroke rehabilitation, to provide a holistic view for nurses and others in providing care. Analysis involved apart‐to‐whole dialectic; selected transcripts, including the bracketing interview, were analyzed in an interpretive research group. There were 14 participants, with a 2‐year median length of time since stroke; participants exhibited various disabilities. The world of the stroke survivor is grounded in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 9 publications
5
94
0
2
Order By: Relevance
“…This is conform with patients' notion that reintegration to community life represents the end point of their rehabilitation process (Lord & Rochester, 2005). But, stroke patients' experience of life after the event is characterized by existential aspects of suffering and loss (Pilkington, 1999;Secrest & Thomas, 1999). Stroke is considered to be a lifetransforming event by those it affects (Brauer, Schmidt, & Pearson, 2001).…”
Section: Introductionsupporting
confidence: 62%
“…This is conform with patients' notion that reintegration to community life represents the end point of their rehabilitation process (Lord & Rochester, 2005). But, stroke patients' experience of life after the event is characterized by existential aspects of suffering and loss (Pilkington, 1999;Secrest & Thomas, 1999). Stroke is considered to be a lifetransforming event by those it affects (Brauer, Schmidt, & Pearson, 2001).…”
Section: Introductionsupporting
confidence: 62%
“…12 Studies that sought to investigate the experience of stroke with reference to the concept of quality of life have reported that survivors relate this to the effects of stroke on their own sense of well-being 72 and to existential aspects of suffering and loss. 73,74 Another focus has been the ways in which patients respond to the changes brought about by stroke. For example, it has been reported that survivors regard following professional advice, making their own care decisions, and staying positive and motivated as important.…”
Section: Life After the Acute Eventmentioning
confidence: 99%
“…The significance of the experience of stroke survivors has been studied previously. [20][21][22][23][24][25][26]. However, the unique point of this study is its focus on significant experiences related to changes in movement caused by hemiplegia.…”
Section: Discussionmentioning
confidence: 99%
“…New indicator of comparing self-worth: motor functions McKevitt et al [27] explains in the review article that effects on stroke survivors are described as 'losses' in previous qualitative studies, as in loss of activity, abilities, personal character, self, and independence; [21][22][23]28] emotional and social loss; [29,30] loss or change of identity. [31][32][33].…”
Section: Changes In Movement and New Self-worthmentioning
confidence: 99%